Pemberdayaan Ekonomi Masyarakat Melalui Penerapan Teknologi Bioflok pada Budidaya Lele di Desa Tasik Seminai, Kabupaten Siak - Amin, Bintal; Efriyeldi, Efriyeldi; Othman, Lie; Zulkifli, Zulkifli; Yolandika, Clara; Rahayunigtyas, Putri; Nurachmi, Irvina; Arief, Hazmi; Pradini, Ulfa Rizki (Unri Conference Series: Community Engagement, 2025)
The community empowerment program utilizing biofloc technology in catfish farming was implemented in Tasik Seminai Village, Siak Regency, with the Pokdakan Tasik Makmur group as the primary partner. The program aimed to enhance the capacity of fish farmers, improve aquaculture techniques, strengthen business management, and generate social and economic benefits at the community level. A participatory approach was implemented through socialization, training, the establishment of a biofloc demonstration pond, and business mentoring over a three month period. Evaluation was conducted using pre- and post-tests, as well as field observations. The results demonstrate significant improvements in farmers’ capacities: knowledge increased from 62% to 85%, positive attitudes toward adopting biofloc rose from 65% to 88%, and technical skills improved from 60% to 82%. Technically, the Feed Conversion Ratio (FCR) decreased from 1.8 to 1.4, while the Survival Rate (SR) increased from 70% to 90%. From an economic perspective, production costs decreased from IDR 23,000,000 to IDR 20,000,000, while net profit increased fivefold, rising from IDR 2,000,000 to IDR 10,000,000. Additionally, the R/C ratio improved from 1.09 to 1.50, indicating enhanced economic feasibility. Socially, the program strengthened group solidarity through collective action and intensive communication. Overall, biofloc technology has proven to be an effective strategic tool for empowering fishing communities by improving technical efficiency, economic viability, and social cohesion in catfish farming.